Color stability comparisons of different type composite resins after curing and when aged in various staining solutions - Yazkan, Basak; Recen, Duygu (Annals of Medical Research, 2021)
Aim: To compare the color stability of two bulkfill (ormocer based or not), two flowable (high and low viscosity) and a universal nanohybrid composite resin after curing and when aged in different staining solutions. Material and Methods: Three hundred twenty discs were made from a low-flowable nanohybrid composite (GrandioSO Heavy Flow), a flowable nanohybrid composite (Grandio Flow), a bulkfill composite (GrandioSO x-tra), an ormocer-based bulkfill composite (Admira Fusion X-tra) and a universal nanohybrid composite (Grandio SO) (n=64). Specimens were subdivided into 4 subgroups, which were immersed in one of the following solutions for 3 hours a day for 30 days: distilled water, filter coffee, red wine and coke (n=16). Color evaluations were done using a dental spectrophotometer at three evaluation stages: immediately before curing, 24 hours after curing and 30 days of staining. Results: After curing; the universal nanohybrid and bulkfill composite showed significantly greater ΔE values than other type composite resins (p0.05). Bulkfill composite was the most stained resin type in all of the staining solution subgroups (p0.05). The bulkfill composite followed by universal and flowable nanohybrid composite and the ormocer based bulkfill composite showed the lowest ΔE values after coffee staining (p0.05). When effects of staining solutions are evaluated; coffee presented the highest staining effect, red wine was the second and, coke and water was the least stained solutions in application to all type of composite resins (p0.05).Conclusions: According to this study, it can be concluded that bulkfill composites showed the least resistance to staining and the ormocers were successful in color stability. In all tested materials, color changes after curing and after coffee staining were clinically perceptible. Therefore, when choosing a particular shade, such possible color changes should be taken into consideration.